Participative Leadership In The Implementation Of Character Education - Cucun Sunaengsih, Purwanto, Aan Komariah, Dedy Achmad Kurniady, (Opción, 2019)
This research find out how a principal applies participative leadership to implement character education. This research describes analysis and exploration as an initial part of four research methodology stages of Design Based Research namely (1) analysis and exploration, (2) design and construction, (3) evaluation and reflection, and (4) implementation and spread. Results of the research show that principal applies participative leadership in decision-making, coordination, motivating, communication and conflict solving for character education implementation. In conclusion, the involvement of CS team is used as an effort of coordination, communication, motivation and decision making for solving problems of conflict and innovation.